2022
DOI: 10.1177/13623613221085364
|View full text |Cite
|
Sign up to set email alerts
|

Measuring subjective quality of life in autistic adults with the PROMIS global–10: Psychometric study and development of an autism-specific scoring method

Abstract: Quality of life is widely acknowledged as one of the most important outcomes in autism research, but few measures of this construct have been validated for use in autistic people. The goal of the current study was to examine the psychometric properties of the Patient-Reported Outcomes Measurement Information System Global–10, an established self-report measure of health-related quality of life, in a sample of 901 autistic adults (predominantly female and adult-diagnosed) recruited from the Simons Foundation Po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 81 publications
1
1
0
Order By: Relevance
“…Moreover, it has been demonstrated that a five-factor structure of the WHOQOL-BREF might be more suitable for characterising QoL in the autistic population than the four-factor structure used in the present study, considering several items (particularly within the social factor) may be interpreted by autistic people differently to their intended meaning ( Mason et al, 2022 ). Replication of our findings using this alternative model of the WHOQOL-BREF, or other suitable measures of QoL (e.g., the Patient-Reported Outcomes Measurement Information System (PROMIS) Global-10 facilitated by a new scoring method for autistic adults; see Williams et al, 2023 ) may help to corroborate the present findings. Additionally, using alternative self-report QoL measures suitable for individuals with intellectual difficulties (e.g., the WHOQOL disabilities module (WHOQOL-DIS); Power & Green, 2010 ) will help to indicate whether our findings extend to individuals across the full autism spectrum.…”
Section: Discussionsupporting
confidence: 71%
“…Moreover, it has been demonstrated that a five-factor structure of the WHOQOL-BREF might be more suitable for characterising QoL in the autistic population than the four-factor structure used in the present study, considering several items (particularly within the social factor) may be interpreted by autistic people differently to their intended meaning ( Mason et al, 2022 ). Replication of our findings using this alternative model of the WHOQOL-BREF, or other suitable measures of QoL (e.g., the Patient-Reported Outcomes Measurement Information System (PROMIS) Global-10 facilitated by a new scoring method for autistic adults; see Williams et al, 2023 ) may help to corroborate the present findings. Additionally, using alternative self-report QoL measures suitable for individuals with intellectual difficulties (e.g., the WHOQOL disabilities module (WHOQOL-DIS); Power & Green, 2010 ) will help to indicate whether our findings extend to individuals across the full autism spectrum.…”
Section: Discussionsupporting
confidence: 71%
“…Others have used a community based participatory research approach with autistic adults to adapt existing instruments for use with autistic participants (Nicolaidis et al, 2020). Other approaches include the application of methods such as item response theory (IRT), structural equation modeling, and network analysis, and even more standard approaches such as test–retest and convergent validity to answer substantive empirical questions about the psychometric properties of both newly‐created and existing PROMs in the autistic population (e.g., Frazier et al, 2022; Mazefsky, Yu, et al, 2018; Schiltz et al, 2019; Schiltz & Magnus, 2020, 2021; Uljarević et al, 2022; Williams et al, 2021; Williams, Cascio, & Woynaroski, 2023). Still others have begun to incorporate PROMs into routine clinical practice, and the first systems of measurement‐based care (Lewis et al, 2018) were recently described within autism research (McFayden et al, 2021; Schwartzman et al, 2023).…”
Section: Progress On Proms In Autism Researchmentioning
confidence: 99%
“…Nevertheless, more research is needed to revise and validate the measure. In another study, Williams et al (2023) developed an autism-specific scoring method for the Patient-Reported Outcomes Measurement Information System Global-10 (PROMIS global-10), which might also be a good tool to assess QoL in autistic adults. However, more research is needed to support these first important findings.…”
Section: Dependentmentioning
confidence: 99%